2019
DOI: 10.1038/s41598-019-55073-2
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent dental arch development among Southern Chinese in Hong Kong: a geometric morphometric approach

Abstract: This study aimed to investigate changes in types of dental arch form during adolescence and explore adolescent changes in size and form of dental arch. Hong Kong Chinese were recruited and digital dental arch models were obtained at ages 12, 15, and 18 years. Geometric morphometrics was used to investigate adolescent changes of dental arch form. There were 225 participants from whom digital models at all three age periods were available. Three types of dental arch form were identified through clustering. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…12,19 The previous studies showed the greatest incremental increases occurred in the maxillary and mandibular anterior and posterior arch widths in both male and female infants during the first 2 years of life, and mandibular intercanine width, on average, was established by 8 years of age. [22][23][24] Our group has concentrated on exploring and addressing the impact on maxilla development caused by palate cleft itself, timing, and protocols of cleft palate repair as well as palatoplasty methods. 12,19,25,26 However, the eventual shape of the maxillary arch architecture after palatoplasty is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…12,19 The previous studies showed the greatest incremental increases occurred in the maxillary and mandibular anterior and posterior arch widths in both male and female infants during the first 2 years of life, and mandibular intercanine width, on average, was established by 8 years of age. [22][23][24] Our group has concentrated on exploring and addressing the impact on maxilla development caused by palate cleft itself, timing, and protocols of cleft palate repair as well as palatoplasty methods. 12,19,25,26 However, the eventual shape of the maxillary arch architecture after palatoplasty is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The size and shape of dental arches and their influence on arch relationships have significant orthodontic implications, as they can affect available space, smile aesthetics, and long-term occlusal stability [ 1 ]. Orthodontic treatment can alter the shape of the dental arch; any changes, however, should not disrupt the balance between bone, dental, and muscular structures, as deviations from the original shape of the dental arch may increase the tendency for treatment to relapse [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic treatment can alter the shape of the dental arch; any changes, however, should not disrupt the balance between bone, dental, and muscular structures, as deviations from the original shape of the dental arch may increase the tendency for treatment to relapse [ 2 ]. The shape of the dental arch is determined by the underlying skeletal morphology, the eruption pathway of teeth, the surrounding soft tissues, and intraoral functional forces [ 1 , 3 ]. Discordance between the shapes of the dental arches may lead to malocclusion.…”
Section: Introductionmentioning
confidence: 99%